Effect of Fear Arousing Messages and Fear of Prosecution on Risky Driving among Drivers in Ghana - Nkansah, A. (University of Ghana, 2013)
Road safety advertisements incorporating fear arousing messages are not uncommon in the media. Years of research into fear appeals has yielded inconsistent results and this notwithstanding, they are usually used as a road safety campaign strategy. In Ghana, where all efforts are being made to reduce traffic accidents, the use of fear arousing messages has not been spared. In an experimental study, the researcher investigated the effectiveness of this message on risky driving attitude and also explored the effect of an alternative strategy, fear of prosecution. The interaction effect that such messages could have with the variables age, gender and driving experience were also examined. Findings from this study suggest that fear arousing messages do not have an independent effect on risky driving. There was also no independent effect for fear of prosecution on risky driving, and even after fear arousing messages and fear of prosecution have been combined, risky driving attitude was not significantly affected. However, the findings indicate that driving experience has an interactive effect with fear arousing messages with drivers with long driving years experience responding positively to fear arousing messages. Drivers with short years of driving experience only responded positively after being exposed to fear of prosecution. Again, age was found to have an interactive effect with fear of prosecution on risky driving attitude, as young drivers reduced their risky driving attitude after watching that message. Fear arousing messages did not have any interactive effect with gender. These findings are used to make conclusions about the design of road safety campaigns incorporating fear arousing messages and fear of prosecution.
Thesis (MPHIL)-University of Ghana, 2013